SISTEM PENGENDALIAN DAN MONITORING KUALITAS AIR TAWAR SERTA PEMBERIAN PAKAN OTOMATIS PADA BUDI DAYA IKAN NILA MENGGUNAKAN NODEMCU ESP-12F - DAVID PARULIAN; Bambang Widodo; Stepanus; Tahan Tobing (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2021)
Indonesia is an aquatic country that has great potential in the field of fish farming. "Minister of Maritime Affairs and Fisheries Edhy Prabowo said that the target for freshwater fish production next year is 4,685,446 tons of the total national aquaculture of 18,440,000 tons in 2020. A total of 4,685,446 tons are freshwater fish commodities such goldfish, tilapia, catfish and carp". The important thing in fish farming is the provision of fish feed and controlling water quality in the pond such as temperature and pH levels in the water. This study aims to design a system that can monitor and control pH and temperature in red tilapia aquaculture ponds. In this study, the system will be tested to get the pH and temperature in the pond by following the Indonesian National Standard, which is in the range of 25°C to 32°C, and the pH level of the water is in the range of 6.5 to 8.5 to produce good water quality for tilapia. Based on the test, it was found that the minimum water pH is 7.29 and the maximum water pH is 8.65, then the time needed to make the pH normal again is 2.5 hours, meanwhile the minimum temperature is 26.5°C and maximum is 31.2°C and still meets the requirements. standard, and for feeding tilapia is 40.57 grams.